The influence of david kolb’s learning style on students’ biology learning achievement - Dewi Asriani Ridzal (Jurnal Pijar Mipa, 2022)
This study aims to know the effect of learning style on the biology learning achievement of class XI students of SMA Negeri 1 Sampolawa. This type of research is ex post facto through a quantitative descriptive approach. The sampling technique is saturated sampling. The sample in the study amounted to 80 students. Research data were obtained through questionnaires and documentation. The data analysis technique is descriptive statistical analysis and inferential statistics through a simple linear regression test. The results showed that descriptively the learning style tendencies owned by class XI students of SMA Negeri 1 Sampolawa were 23 students with Diverging learning styles with a percentage of 28.8%, Assimilating as many as 20 students with a percentage of 25.0%, Converging as many as 19 students with the percentage are 23.8%. The Accommodating is 18 students with a percentage of 22.5%. Based on the results of the inferential analysis, a significance value of 0.003 was obtained, which was smaller than the value of equal to 0.05, meaning that David Kolb’s learning style had a positive and significant effect on students' learning achievement in biology.